2020
DOI: 10.1080/23311975.2020.1818368
|View full text |Cite
|
Sign up to set email alerts
|

Ethical entrepreneurial leadership and organizational trust for organizational sustainability

Abstract: This study aims to examine and analyze the role of ethics in entrepreneurial leadership, and its influence on organizational trust and organizational sustainability. This study also analyzes the role of organizational trust in mediating the relationship of ethical entrepreneurial leadership to organizational sustainability. This research was conducted at the Village Credit Institution (Lembaga Perkreditan Desa/LPD) in Bali. The total population of active LPD in Bali in 2018 was 1,422 units. The number of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
1
16
0
1
Order By: Relevance
“…The outcomes of this research also demonstrated a positive impact of trust on OS ( β = 0.167, t = 6.615), indicating that the workforce's trust in their higher-ups leads to sustainability of their workplace. This result provides further support to the study carried out by Sarmawa et al (2020), who found that trust exerted positive effect on sustainability. The outcomes of this work indicate that the presence of trust is the foundation of constructive activities carried out inside and outside the organization (e.g.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The outcomes of this research also demonstrated a positive impact of trust on OS ( β = 0.167, t = 6.615), indicating that the workforce's trust in their higher-ups leads to sustainability of their workplace. This result provides further support to the study carried out by Sarmawa et al (2020), who found that trust exerted positive effect on sustainability. The outcomes of this work indicate that the presence of trust is the foundation of constructive activities carried out inside and outside the organization (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Whilst spirituality (e.g. SI) necessitates trust to exist (Terzi et al , 2020) for sustainability (Sarmawa et al , 2020). Furthermore, EI can build trust among organizational members to tackle crisis situations and generate an efficient working environment (Porter, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The long-term effect of authentic leadership that does not prioritize ethics, service, and transformation actually hampers work performance significantly [73]. It is a whip in authentic leadership that does not change the quality of job performance.…”
Section: Discussionmentioning
confidence: 99%
“…The sustainability of a company is determined by complex factors, both internal and external. Internal factors that can affect business sustainability include support for corporate resources including human resources and leadership patterns (Sarmawa et al 2020), corporate governance, and environmental/corporate climate management. External factors include customer trust and loyalty, socio-economic conditions, and government participation.…”
Section: Theoretical Review Previous Research and Hypothesis Business Sustainabilitymentioning
confidence: 99%